EVALUASI PERESEPAN OBAT MASA PANDEMI DAN PASCA PANDEMI COVID-19 DI PUSKESMAS LOSARANG - Anis Febri Nilansari; Puja Alfin Fadillah (Jurnal Buana Farma, 2024)
Pharmaceutical services play a crucial role in patient therapy success, with prescribing errors being a common issue leading to treatment failure. The COVID-19 pandemic, caused by the coronavirus, has underscored the need for evaluating drug prescriptions during and after the crisis. This study, conducted at the Losarang Community Health Center, Indramayu Regency, aims to assess prescription patterns and drug suitability based on WHO indicators. Using a retrospective approach, patient prescriptions from July to December 2020 (pandemic) and July to December 2023 (post-pandemic) were analyzed. Results indicate notable differences in prescribing trends. During the pandemic, antivirals, antibiotics, analgesics, and vitamins were commonly prescribed, whereas post-pandemic, analgesics, antibiotics, antihypertensives, antihyperglycemics, and antacids saw increased prescription rates. However, the average number of drugs per prescription sheet exceeded WHO standards during both periods, indicating potential inefficiencies. While the percentage of generic drug prescriptions met standards (100%), antibiotic prescriptions did not comply during both phases (pandemic: 100%, post-pandemic: 44.03%). Injection preparations met WHO standards (<20%) for both periods. Notably, adherence to the health center formulary was consistent with standards (100%) during both phases. In conclusion, this research underscores the need for optimizing prescribing practices to enhance patient outcomes. Strategies to reduce the number of drugs per prescription and ensure appropriate antibiotic use are imperative, emphasizing adherence to WHO guidelines and formulary recommendations.